2019
DOI: 10.5194/amt-12-1429-2019
|View full text |Cite
|
Sign up to set email alerts
|

A method for extracting calibrated volatility information from the FIGAERO-HR-ToF-CIMS and its experimental application

Abstract: Abstract. The Filter Inlet for Gases and AEROsols (FIGAERO) is an inlet specifically designed to be coupled with the Aerodyne High-Resolution Time-of-Flight Chemical Ionization Mass Spectrometer (HR-ToF-CIMS). The FIGAERO-HR-ToF-CIMS provides simultaneous molecular information relating to both the gas- and particle-phase samples and has been used to extract vapour pressures (VPs) of the compounds desorbing from the filter whilst giving quantitative concentrations in the particle phase. However, such extraction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 37 publications
1
71
0
Order By: Relevance
“…2). We surmise that β-phellandrene must have a high SOA yield, possibly comparable to that of dlimonene, which has been reported in the range of 50 %-60 % (Berg et al, 2013;Lee et al, 2006;Surratt et al, 2008) and which shares some structural similarity with βphellandrene (Fig. 2).…”
Section: Soa Mass Yieldssupporting
confidence: 69%
“…2). We surmise that β-phellandrene must have a high SOA yield, possibly comparable to that of dlimonene, which has been reported in the range of 50 %-60 % (Berg et al, 2013;Lee et al, 2006;Surratt et al, 2008) and which shares some structural similarity with βphellandrene (Fig. 2).…”
Section: Soa Mass Yieldssupporting
confidence: 69%
“…Beijing regularly experiences periods of very high particle pollution, with annual and 24 hr levels well above the World Health Organization guidelines (Chan et al, 2008;Hu et al, 2014). Premature mortality, as a result of respiratory illness, cardiovascular disease and cancer, has been associated with exposure to poor air quality (Dockery et al, 1993;Pope et al, 2000;Pope and Dockery, 2006;Jerrett et al, 2009;Beelen et al, 2014;Laurent et al, 2014;Ostro et al, 2015). Lelieveld et al (2015) estimated that 1.36 million premature deaths in China in 2010 were a result of exposure to outdoor air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…These data provide thermal desorption profiles that have been previously used to draw conclusions about the volatility distribution of ions. However, we do not make use of this in this study owing to the additional complexity associated with the calibration of the volatility and uncertainties with thermal decomposition (Bannan et al, 2019;Schobesberger et al, 2018;Stark et al, 2017); instead, we integrate these desorption profiles in order to compare the overall composition of the different precursors. For all plant and VOC experiments, > 70 % of observed product signal was assigned with molecular formulae, and these ions are used for analysis in the following.…”
Section: Figaero-i-hr-tof-cims Measurementsmentioning
confidence: 99%
“…Mehra et al: Oligomer and HOM formation from oxidation of oxygenated monoterpenes The formation of highly oxygenated organic molecules (HOMs) has been identified as a pathway for new particle formation (NPF) and growth of SOA (Bianchi et al, 2019;Ehn et al, 2014). Recent work has shown that alongside HOM formation from ozonolysis (Quéléver et al, 2019), hydroxyl radical oxidation of monoterpenes is a large source of HOMs (Berndt et al, 2016). Oligomerisation is another key pathway to formation of SOA and has been identified as important for monoterpenes including α-pinene and limonene (Hall and Johnston, 2011;Kourtchev et al, 2016;Kundu et al, 2012;Putman et al, 2011;Tolocka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%